Global virtual teams’ (GVTs) performance: online training and development, organizational commitment, and motivation - Gheni, Ali Yahya; Jusoh, Yusmadi Yah; A. Jabar, Marzanah; Mohd. Ali, Norhayati (INSInet Publication, 2016)
The global virtual teams (GVTs) comprise of team members who are geographically dispersed, culturally varied, and mainly depends on information and communication technologies (ICT) to communicate with each other's. In spite of technological leverages, the GVTs facing many challenges that affect their performance. Hence, the online training and development is very important for GVTs to perform. The main goal of online training and development is to improve the skills and behaviors of the GVTs, which leads to increase the performance of the team. A systematic literature review was conducted to answer two research questions. The first research question is to investigate the relationship between online training and development and global virtual teams' performance. The second research question is to find out the existing frame works involving online training and development in GVTs. Then, the related frameworks are analyzed to highlight the gaps and limitations for each of them. The findings indicated that there is a positive relationship between online training and development and global virtual teams' performance. The existing frameworks are overlapped in some variables such as online training and global virtual teams' performance. However, the existing frameworks are still not sufficient to measure the performance of GVTs. A Performance Measurement Framework for GVTs was proposed to assist the project manager on measuring the global virtual teams' performance involving the online training and development, organizational commitment, and motivation based on defined key performance indicators (KPIs).